2013
DOI: 10.1186/1471-2202-14-26
|View full text |Cite
|
Sign up to set email alerts
|

Apurinic/apyrimidinic endonuclease 1 is a key modulator of aluminum-induced neuroinflammation

Abstract: BackgroundChronic administration of Aluminum is proposed as an environmental factor that may affect several enzymes and other biomolecules related to neurotoxicity and Alzheimer's disease (AD). APE1 a multifunctional protein, functions in DNA repair and plays a key role in cell survival versus cell death upon stimulation with cytotoxic agent, making it an attractive emerging therapeutic target. The promising protective effect of resveratrol (resv), which is known to exert potent anti-inflammatory effects on ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 46 publications
2
45
0
Order By: Relevance
“…Resveratrol (trans-3′,4′,5-trihydroxystilbene), an essential polyphenolic cancer prevention agent present in grapes and other dietary parts, shows antiproliferative action against growth cells in vitro studies (Wong et al 2011). Resveratrol additionally assumes a vital part in the counteractive action of anxiety by regulating APE/Ref-1 (Zaky et al 2013). In this, the antioxidant effect of LBC (Teng et al 2016) and FnC 60 (Andrievsky et al 2009) may be hidden mechanism by which both of these components diminished the expression of APE-1/Ref-1, which is principally invigorated by oxidative anxiety (Zaky et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol (trans-3′,4′,5-trihydroxystilbene), an essential polyphenolic cancer prevention agent present in grapes and other dietary parts, shows antiproliferative action against growth cells in vitro studies (Wong et al 2011). Resveratrol additionally assumes a vital part in the counteractive action of anxiety by regulating APE/Ref-1 (Zaky et al 2013). In this, the antioxidant effect of LBC (Teng et al 2016) and FnC 60 (Andrievsky et al 2009) may be hidden mechanism by which both of these components diminished the expression of APE-1/Ref-1, which is principally invigorated by oxidative anxiety (Zaky et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Past information has demonstrated the inclusion of APE1 adjustment in the pathogenesis of numerous disarranges, including liver fibrosis (Bassiouny et al 2011a), liver cirrhosis (Bassiouny et al 2011b) ,neuroinflammation (Zaky et al 2013) and different cancers (Chen et al 2013). The multiplication of eukaryotic cells regularly includes a methodical movement through four unmistakable periods of the cell-cycle: G1, S, G2, and M (Obaya and Sedivy 2002).…”
Section: Page 2 Of 32mentioning
confidence: 99%
“…Previous studies have demonstrated a role for Al in dementia (8), PD (9) and AD (10). Furthermore, an aluminum chloride (AlCl 3 )-induced model has previously been established for the investigation of neurotoxicity (11), AD (12), dementia (13), and neuroinflammation (14).…”
Section: Introductionmentioning
confidence: 99%
“…Reports have also defined it as an important etiological factor in the progression of several neurodegenerative disorders as it influences more than 200 biologically important reactions (6,7). Aluminium-induced brain toxicity was reported in rats by many authors, including administration of aluminium chloride hexahydrate (25 mg kg -1 day -1 ) for one month by oral gavage (8), daily oral treatment with aluminium chloride (100 mg kg ) orally for four consecutive weeks (9,10). The neurotoxicity of Al is likely to be the result of a combination of several mechanisms, including oxidative brain injury, induction of apoptosis and neuronal damage, neuroglia inflammatory reaction, and reduced neurotransmitter biosynthesis (6,11).…”
mentioning
confidence: 99%